2013
DOI: 10.1016/j.jagp.2013.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life Mental Health Education for Workforce Development: Brain Versus Heart?

Abstract: Purpose There is a shortage of mental health professionals to care for a growing geriatric population. Though not mutually exclusive, clinical and didactic educational experiences promote cognition, while affective knowledge (attitude) is promoted through non-clinical exposure to seniors. This study evaluates the relative impact of cognition and attitude on career interests among healthcare students. Methods We developed thirteen interactive, video-documentary “lessons” on late-life mental health presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…See Figure 7 for the comparison result between the expected value of the sample and the actual output value of the model. The system of reference [13] The system of reference [16] This paper system It can be seen from all the data that the modeling of psychological well-being based on BPNN has good accuracy and adaptability, the error of the modeling results is small, the fitting is good, and the modeling results are obviously better than those of CNN. In this paper, through the effective combination of the two algorithms, the advantages of the two algorithms are complementary.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Figure 7 for the comparison result between the expected value of the sample and the actual output value of the model. The system of reference [13] The system of reference [16] This paper system It can be seen from all the data that the modeling of psychological well-being based on BPNN has good accuracy and adaptability, the error of the modeling results is small, the fitting is good, and the modeling results are obviously better than those of CNN. In this paper, through the effective combination of the two algorithms, the advantages of the two algorithms are complementary.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…In order to further optimize the model recognition effect, Downs et al proposed a psychological well-being problem recognition algorithm based on the DeepPsy model [ 15 ]. Combining with the current situation and characteristics of the student group, Rosen et al expanded the evaluation factors by analyzing the reasons that affect the students' psychological well-being; they collected the corresponding data and used the NN model to predict and analyze the students' psychological well-being status [ 16 ]. Levecque et al revealed the main countermeasures and approaches for college students' psychological well-being education from the aspects of higher education authorities, university management, teachers, campus cultural environment, and the relationship between psychological well-being education and ideological and political education [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…The seclusion environment holds risk factors for tripping, slipping, and stumbling for patients who have mobility difficulties or have been sedated. Small environmental changes such as floor materials, lighting, and removal of doorsteps could help reduce risk factors for falls as extrinsic, environmental factors account for a significant proportion of falls 40. The findings of this study can be used to provide a basis for such interventions; the model can be used to steer the focus on the most significant risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The mobility and instability of the elderly migrant population make their mental health easy to neglect [21]. Mental health education helps aging individuals understand basic knowledge about their psychological cognition and develop basic skills and methods to deal with psychological problems, prevent negative attitudes and reduce negative emotions such as anxiety and depression, which helps to enhance their physical and mental health [22][23][24][25]. Generally, the results of this study demonstrated that the average acceptance rate of mental health education among the elderly migrant population aged ≥ 60 years in China was 29.2%.…”
Section: Discussionmentioning
confidence: 99%